Wide skin markings pattern: melanoma descriptor or patient‐related factor?. (23rd March 2018) - Rishpon, A.; Marchetti, M.; Marghoob, A.
Abstract : Linked Article: Bassoli et al. Br J Dermatol 2018;178 :e217–e218.